2005
DOI: 10.1248/bpb.28.1054
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Hypericin across Chick Chorioallantoic Membrane and Photodynamic Therapy Vasculature Assessment

Abstract: Photodynamic therapy (PDT) utilizes a photosensitizer for the treatment of superficial cancers. Hypericin (HY; a naphthodianthrone, MW 504.45; Fig. 1) is a potent and promising photosensitizer found in the plant, Hypericum perforatum, commonly known as St. John's wort.1) HY exhibits a bright fluorescence with potent photosensitizing properties. It was reported to be useful for the detection of bladder carcinoma in situ, with a sensitivity and specificity of 94% and 95% respectively.2) Recent studies in our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
(30 reference statements)
0
15
0
1
Order By: Relevance
“…p values lower than 0.05 were considered significant. Nonparametric statistical Mann-Whitney U test of the qPCR results for the in vivo animal study was performed using SPSS software (version 17, USA) (33,34).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…p values lower than 0.05 were considered significant. Nonparametric statistical Mann-Whitney U test of the qPCR results for the in vivo animal study was performed using SPSS software (version 17, USA) (33,34).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The PDT showed therapeutic effects not only by immunomodulation but also by vascular destruction of the targeted lesion. Several studies have reported on the vascular effects of PDT [10][11][12] . It has been suggested that topical PDT has a pronounced effect on the microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…The chorioallantoic membrane of chicken eggs is known as CAM and is probably the most used in vivo model to study angiogenesis and compounds activities in vascular endothelium. With a direct access to blood vessels and embryo, this model is simple, cheap and of easy implementation in laboratory environment [15][16][17].…”
Section: Introductionmentioning
confidence: 99%